Design of a multi-level inverter for solar power systems with a variable number of levels technique - Mohammed A. Qasim; Vladimir Ivanovich Velkin; Mustafa Fawzi Mohammed; Alaa Ahmad Sammour; Yang Du; Sajjad Abdul-Adheem Salih; Baseem Abdulkareem Aljashaami; Sharipov Parviz Gulmurodovich (Institute of Advanced Engineering and Science, 2023)
Overall harmonic distortion and losses will grow during an energy conversion process, while power stability will be reduced. Multilevel inverter technologies have recently become very popular as low-cost alternatives for a variety of industrial purposes. The design's minimal benefits include reduced component losses, decreased switching and conduction losses, along with enhanced output voltage and current waveforms. Also, a reduction of the harmonic components of the current and output voltage of the inverter are the most important requirements in multilevel inverters. A seven-level inverter design is presented in this paper that is simulated using MATLAB/Simulink. The inverter converts the DC voltage from three photovoltaic (PV) systems into AC voltage at seven levels. During an outage of one of the PV systems, the inverter will make a switching reduction and supply the AC voltage as a five-level inverter. The inverter’s total harmonic distortion (THD) when it performs as a five-level or seven-level inverter is 4.19% or 1.13% respectively. The modulation technique used is phase disposition via four carriers and a single reference signal at the fundamental frequency.